2010
DOI: 10.1177/0306624x10382570
|View full text |Cite
|
Sign up to set email alerts
|

Can a 12-Step Program Work in Methadone Maintenance Treatment?

Abstract: Three consecutive, professionally led (as opposed to self-help) groups following the 12-step program (TSP) were integrated into a methadone maintenance treatment (MMT) program that included 32 heroin-addicted individuals in recovery. This report describes our experience in meeting the challenges that arose and our conclusions regarding the therapeutic potential of this integration. A professional therapeutic staff guided the groups. In-depth interviews of 10 participants and the reflections of the group leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…It might be possible to respond to this by means of outreach programs that include various techniques to improve the continuity of care, such as therapist-initiated telephone calls (McKay et al, 2004), assertive monitoring, or early re-intervention McKay, 2009). Moreover, it is especially important to expand a social support alternative for women that is not based on NA, which is not always suitable for women (Kruk & Sandberg, 2013) and does not accept clients of methadone maintenance treatment, leaving these recovering addicts especially vulnerable to lack of social support and hence prone to relapse (Ronel, Gueta, Abramsohn, Caspi, & Adelson, 2011). Second, gender-sensitive therapies should not only include issues of drug abstinence but also help women deal with daily life, by means of, for instance, acquiring a profession, managing finances, and housing.…”
Section: Discussionmentioning
confidence: 99%
“…It might be possible to respond to this by means of outreach programs that include various techniques to improve the continuity of care, such as therapist-initiated telephone calls (McKay et al, 2004), assertive monitoring, or early re-intervention McKay, 2009). Moreover, it is especially important to expand a social support alternative for women that is not based on NA, which is not always suitable for women (Kruk & Sandberg, 2013) and does not accept clients of methadone maintenance treatment, leaving these recovering addicts especially vulnerable to lack of social support and hence prone to relapse (Ronel, Gueta, Abramsohn, Caspi, & Adelson, 2011). Second, gender-sensitive therapies should not only include issues of drug abstinence but also help women deal with daily life, by means of, for instance, acquiring a profession, managing finances, and housing.…”
Section: Discussionmentioning
confidence: 99%
“…In response to this unaccepting attitude on the part of NA, there have been some efforts to develop 12-step fellowships that are accepting of methadone patients (i.e., “Methadone Anonymous”), but despite some encouraging applications (Nurco, Stephenson, & Hanlon, 1990-91; Ronel, Gueta, Abramsohn, Caspi, & Adelson, 2011), their diffusion has been very limited relative to AA or NA. Although leading researchers in the addiction treatment field have argued that 12-step addiction recovery and opioid agonist maintenance are not incompatible (White et al, 2012; White & Mojer-Torres, 2010; Betty Ford Institute Consensus Panel, 2007), the reality is that opioid agonist treatment patients attending NA meetings for support are likely to experience conflicts and pressures to discontinue their medication (Parran et al, 2010).…”
Section: 0 Introductionmentioning
confidence: 99%
“…Unfortunately for many patients in opioid agonist treatment, there is often a struggle surrounding the compatibility of utilizing a medication for their dependence and the 12-step literature, mission, and programming (Natti Ronel et al, 2011). Although both 12-step approaches and opioid agonist treatments view addiction as a chronic disease (Dole & Nyswander, 1967; N Ronel, 1999; W.…”
Section: 0 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, a study was conducted to examine the impact of 12-step treatment on heroin-addicted people, who were treated with methadone. Results showed that people achieved a sense of self-efficacy and were motivated to change their life style (25) the treatment of drug use. Although the results of the studies have shown that a significant correlation was found between spirituality and mental health of the people in the treatment stages using AA method, this process requires people completing the 12-steps treatment so that they can advocate it for others (26).…”
Section: Discussionmentioning
confidence: 99%